Modeling Mercury Flows in Thailand on the Basis of Mathematical Material Flow Analysis. Issue 1 (2nd December 2015) - Wongsoonthornchai, Manaporn; Kwonpongsagoon, Suphaphat; Scheidegger, Ruth
Abstract : Mercury pollution is a global problem, because it can be transported across borders and released from both natural and anthropogenic sources. In this paper, we studied the mercury flows in Thailand originating from anthropogenic sources (from intentional and unintentional use) in 2010, giving for the first time a comprehensive overview over mercury stock and flows including emissions in Thailand. Mathematical material flow analysis was applied to calculate the stock of mercury and its flows in the country. All available data from various sources such as statistical data, literature, surveys, and interviews with experts were used. The results showed that total mercury emissions were about 57 000 kg/year, 61% of them to land, 35% to air, and 4% to water. The largest mercury input comes as impurities in imported zinc, followed by domestically mined gold ores in which mercury is also an impurity. The largest stock of mercury is found in dental amalgam, followed by air conditioners and sphygmomanometers. The scenarios developed here were designed to reduce mercury emissions. Unintentional use alone can reduce total mercury emissions by about 33%, while around 5% of the potential reduction comes from intentional use. Changes in combined unintentional and intentional use can lead to the highest potential reduction. Abstract : Mercury pollution is a global problem because it can be transported across long distances and across borders to other countries from both natural and anthropogenic sources. Here, mathematical material flow analysis (MMFA) was applied to gain system knowledge over Hg flows in Thailand. The results show the first time a comprehensive overview over mercury stock and flows including emission in a developing country, like Thailand.